Innuendo in Music as an Active Perception Factor - Stronko, Boryslav (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2022)
Relevance of the study. A problem, discussed in the article is listener’s co-activity in the process of perception music. Communicative aspects of art were deeply and variously studied in many musicologists’ works. But item of listener’s co-participation in phenomena of tension between potential, most probable way of composer’s thought (from one side) and the real sounding of musical composition (from another side) is not completely explored. Phenomena of music is considered as a dialogue among composition and listener’s consciousness, in spite of traditional view to music as a composer’s monologue only. Main objective is to reveal the communicative and aesthetic potential of innuendo in music. One of the most significant expedients in this sphere of thinking is innuendo. In the context of recent paper this notion is treated as absence of the most waited music material as a specific mean, which causes more sharp and strong perception of tide of sounds. Methodology. Methods of this study are: conditional comparative analysis of a music compositions’ set; modeling of listener’s expectations from music; reconstruction of composers’ design, using the author’s experience of composing. These methods were explored in the modeling of listener’s perception of the several music compositions of different styles. The results and conclusions. Contemporary academic concert music, as a rule, means a division to active music makers (e.g. composer, improviser, performer) and passive listener. However, even in art styles the vivid link between piece of music and public contains hidden interactivity of listener. It may be a relict of co-participation in music performance in the folk and church traditions. There is no real interactivity in art genres because of listener’s impossibility to intervene into real sounding structures. But in the context of certain style advanced listener has an opportunity to feel the difference between most probable and real composer’s variants of continuation. Listener is presented as a reconstructor of composer’s ideas, of course, in cause of his knowledge of present style. Such expectations of listener belong to functionality in music. Innuendo is effect of pseudodeconstruction, based on the functional expectations system. There are such types of music innuendo as: 1) vertical (absence of expected texture component); 2) horizontal (absence of expected continuation); 3) active (by disruption of expected continuation); 4) passive (absence without disruption); 5) provocative (incompleteness as an occasion to maintain more complete version of present theme). Absence as a kind of Presence (Heidegger) is an ontological basis of innuendo effect, because it is replaced full Presence as real in the place of expected. Thereby reality of this fragment isn’t absolute but one from set of possibilities. Dialogue between "Listener’s Variant" and "Composers variant" is a realization of ontological time’s potential, which contains more than one option in future.